Analgesic effect of ketorolac added to lidocaine in surgery of traumatic arm injuries: A double-blind, randomized clinical trial - Afshin Amini; Arash Farbod; Mohamad Hosein Eghbal; Maryam Ghadimi; Ensiyeh Shahriyari (European Journal of Translational Myology, 2022)
Acute pain after surgery can cause harmful effects. There are many ways to treat pain after surgery. Bier block technique is also a type of intravenous regional anesthesia that is suitable for short and minor surgeries of the arm, wrist, and fingers, so this study aims to compare the analgesic effect of Ketorolac in intravenous injection and when the lidocaine is added to Bier block. In surgery, traumatic injuries to the upper limbs. This study was a clinical trial, randomized and double-blind. The target population was candidates for upper limb orthopedic surgery. The patients selected based on the entry and exit criteria were randomly assigned to one of the 3 study groups. The intensity of pain, the amount of morphine consumed through the intravenous PCA pump, the incidence of side effects of morphine and ketorolac, as well as the overall patient satisfaction regarding the anesthesia method and pain control were compared between the groups. Data analysis, both descriptive and analytical, was done using SPSS statistical software version 21. The three studied groups were identical and had no differences in terms of quantitative and qualitative demographic variables. The median tourniquet closing time is different between the control group and the intravenous ketorolac and topical ketorolac groups with P=0.002 and P=0.001, respectively. There was no significant difference between the three groups in terms of the time of the first request to receive painkillers after deflating the tourniquet, but the amount of morphine received between the groups was significantly different (P=0.02). Comparison of pain intensity based on NRS, considering Taking the measurement repetition times indicated the significance of the effect of pain intensity between the groups (P=0.001). In terms of overall satisfaction with the quality of analgesia and anesthesia method, no significant difference was observed between the three study groups. In terms of the occurrence of complications related to the use of ketorolac, no complications were observed in any of the groups receiving this drug.